2008
DOI: 10.1145/1353445.1353451
|View full text |Cite
|
Sign up to set email alerts
|

PEAK—a fast and effective performance tuning system via compiler optimization orchestration

Abstract: Compile-time optimizations generally improve program performance. Nevertheless, degradations caused by individual compiler optimization techniques are to be expected. Feedback-directed optimization orchestration systems generate optimized code versions under a series of optimization combinations, evaluate their performance, and search for the best version. One challenge to such systems is to tune program performance quickly in an exponential search space. Another challenge is to achieve high program performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Moreover, it is independent of the solution-space, the search algorithm and the compiler/optimizer used. PEAK, an automated performance tuning system is presented in [26]. It uses three heuristic algorithms to select good compiler optimization settings.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, it is independent of the solution-space, the search algorithm and the compiler/optimizer used. PEAK, an automated performance tuning system is presented in [26]. It uses three heuristic algorithms to select good compiler optimization settings.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, it is independent of the solution-space, the search algorithm and the compiler/optimizer used. PEAK, an automated performance tuning system is presented in [35]. It uses three heuristic algorithms to select good compiler optimization settings.…”
Section: Related Workmentioning
confidence: 99%
“…Haneda et al employed statistical analysis of the effect of compiler options to prune the phase selection search space and find a single compiler setting for a collection of programs that performs better than the standard settings used in GCC [11]. Pan and Eigenmann developed three heuristic algorithms to quickly select good compiler optimization settings, and found that their combined approach that first identifies phases with negative performance effects and greedily eliminates them achieves the best result [22]. Also related is the work by Fursin et al who develop a GCC-based framework (MILEPOST GCC) to automatically extract program features and learn the best optimizations across programs.…”
Section: Background and Related Workmentioning
confidence: 99%